Preface: 5th International Symposium on Frontiers of Economics and Management Science (FEMS 2024) - Yin, Muyi; Xu, Thomas (Transactions on Economics, Business and Management Research, 2024)
It was a great pleasure to welcome you to 5th International Symposium on Frontiers of Economics and Management Science (FEMS 2024), which had been held successfully during April 13-14, 2024 in Macao, China. The organizing committees are very grateful indeed to the presence of Prof. W. Wang who from Central China Normal University, and Prof. W. Yue from University of Bedfordshire. We also wish to thank the plenary and invited speakers: Prof. S, Karsten from University of Waterloo, Canada, Prof. G.S. Liu from Hunan University, Prof. S. Zhu from Wuhan University, Prof. P. Wang from Guangzhou College of Commerce. FEMS 2024 had gained respect in the scientific community with consistent hard work of its organizers. The objective of publishing this proceedings is to record, acknowledge, and share the cherished contribution made by the symposium participants. With our warmest regards, Conference Committees